Case Study : Acceptance and Adoption on E-Commerce Usage Among Micro Business Owner at Baazar Larut Malam Jalan Lee Sam in Seremban Negeri Sembilan - Fatimah , Talip (2011)
This study aims to determined the level of acceptance and adoption of e-commerce usage among micro business owner at baazar larut malam Jalan Lee Sam, Seremban Negeri Sembilan. Recent statistics show that total number of businesses employing web sites in Seremban is very small compared to others city in our beloved country Malaysia. Organizations are coming under increasing pressure to adopt electronic commerce as part of the need to be efficient and competitive and to play a greater role in driving the economy.With the new century,the continued prosperity of Malaysia can no longer be taken for granted.Qualitative research method,in the form of semi-structured interviews, was used to identify factors that are important and relevant to encourage willingness to adopt. Findings indicate that owner characteristics like lack of perceived benefits,lack of knowledge and skill,perceived lack of trust are significant inhibitors while environment characteristics like competitive pressure,government support and infrastructure are significant motivators of electronic commerce in Malaysia. The model forms a basis for further research as further quantitative study,in the form of survey, can be carried out to assess the model’s validity and provide further insights into the relationships among the factors.